2020
DOI: 10.1007/s10029-020-02124-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after contaminated complex abdominal wall reconstruction

Abstract: Purpose Complex abdominal wall repair (CAWR) in a contaminated operative field is a challenge. Available literature regarding long-term outcomes of CAWR comprises studies that often have small numbers and heterogeneous patient populations. This study aims to assess long-term outcomes of modified-ventral hernia working group (VHWG) grade 3 repairs. Because the relevance of hernia recurrence (HR) as the primary outcome for this patient group is contentious, the need for further hernia surgery (FHS) was also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…Multiple studies investigating the use of biologic mesh in high-risk patients and/or contaminated hernia repair found that most postoperative wound complications can indeed be managed conservatively, and the number of patients that develop mesh infection requiring removal is as low as 0% in non-crosslinked biologic mesh [ 3 , 5 7 ]. However, reported hernia recurrence rates could be as high as 30% after 3 years [ 7 , 8 ]. These results combined with the high purchase costs of biologic meshes have led to a search in alternative meshed to be used in complex AWR (CAWR).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies investigating the use of biologic mesh in high-risk patients and/or contaminated hernia repair found that most postoperative wound complications can indeed be managed conservatively, and the number of patients that develop mesh infection requiring removal is as low as 0% in non-crosslinked biologic mesh [ 3 , 5 7 ]. However, reported hernia recurrence rates could be as high as 30% after 3 years [ 7 , 8 ]. These results combined with the high purchase costs of biologic meshes have led to a search in alternative meshed to be used in complex AWR (CAWR).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported safe use of biologic mesh reinforcements in contaminated ventral hernia repair. 15,16 Our patient underwent open inguinal hernia repair with removal of the gallstone via an enterotomy, that was subsequently closed. The hernia was reduced and following an orchidectomy, the posterior wall of the inguinal canal was reinforced with a biological mesh.…”
Section: Discussionmentioning
confidence: 97%
“…En nuestro caso se obtuvieron adecuados resultados en el paciente, por lo que pudo egresar sin complicaciones, y si bien se requieren estudios más grandes para emitir algún tipo de recomendación en este tipo de casos, se conoce que el 32.2% en que se realiza alguna otra cirugía adicional presentan recurrencia al realizar alguna cirugía adicional abdominal 9 , por lo que es necesario tener un adecuado protocolo de selección de pacientes, que deben tener un adecuado control de cualquier comorbilidad, como en el caso expuesto, y la corrección de cualquier factor modificable que pudiera aumentar el riesgo quirúrgico per se.…”
Section: Discussionunclassified